Traceability analysis and process emission reduction of pollutants in petrochemical wastewater under low-carbon constraints - TANG Anzhong; DI Xuemei; CHEN Jiaming (Gongye shui chuli)
Under the “dual carbon” goal, the article creatively proposed industrial water use, sewage discharge, sewage collection and transportation, sewage treatment and reuse of petrochemical enterprises should be treated as a complete system. Taking into account the characteristics of pollution discharged from production units,and the generation and emission path of pollutants, a sewage system pollutant traceability analysis platform was constructed to accurately analyze the discharge of various pollutants and total emissions of pollutants, realize pollution source localization, and optimize the source and process emission reduction. Taking a certain petrochemical enterprise as an example, the platform application in the actual operation of the sewage system was demonstrated. The results indicated that the application of pollutant tracing analysis and process reduction technology could achieve online monitoring, operational analysis, pollution source tracing, and source reduction of sewage discharge, which effectively reduced the water quantity and pollutant concentration entering sewage treatment plants, and provided conditions for optimizing operation and energy conservation and carbon reduction.